2017
DOI: 10.1245/s10434-017-5963-7
|View full text |Cite
|
Sign up to set email alerts
|

Expanded Gene Panel Use for Women With Breast Cancer: Identification and Intervention Beyond Breast Cancer Risk

Abstract: BackgroundClinicians ordering multi-gene next-generation sequencing panels for hereditary breast cancer risk have a variety of test panel options. Many panels include lesser known breast cancer genes or genes associated with other cancers. The authors hypothesized that using broader gene panels increases the identification of clinically significant findings, some relevant and others incidental to the testing indication. They examined clinician ordering patterns and compared the yield of pathogenic or likely pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 38 publications
(32 reference statements)
3
43
1
Order By: Relevance
“…Among those patients with mutations, 78 patients (77.2%) had a BRCA1/2 AJ founder mutation, 3 patients (3.0%) had a nonfounder BRCA1/2 mutation, and 20 patients (19.8%) had a mutation in a gene other than BRCA1/2. 28,29 These findings have led many to conclude that comprehensive testing provides complete relevant genetic information for highrisk AJ patients. Of the 101 patients with pathogenic mutations, 23 patients (22.8%) would have had a missed opportunity for the diagnosis of a cancer-associated mutation using BRCA1/2 founder mutation testing alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those patients with mutations, 78 patients (77.2%) had a BRCA1/2 AJ founder mutation, 3 patients (3.0%) had a nonfounder BRCA1/2 mutation, and 20 patients (19.8%) had a mutation in a gene other than BRCA1/2. 28,29 These findings have led many to conclude that comprehensive testing provides complete relevant genetic information for highrisk AJ patients. Of the 101 patients with pathogenic mutations, 23 patients (22.8%) would have had a missed opportunity for the diagnosis of a cancer-associated mutation using BRCA1/2 founder mutation testing alone.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the prevalence of non-BRCA1/2 mutations in AJ cohorts is not very different from rates reported in the general population. 28,29 These findings have led many to conclude that comprehensive testing provides complete relevant genetic information for highrisk AJ patients. 20 However, others have challenged the assertion that large multigene panels are appropriate for AJ patients.…”
Section: Discussionmentioning
confidence: 99%
“…(b) Recent research supports BRCA testing in a broader range of individuals, if not in every breast cancer patient. This recommendation is based on the findings of studies that conclude that the traditional approach may miss up to 50% of mutation carriers [5,6].…”
Section: Clinical Criteria For Germline Testing In Hobc Risk Assessmentmentioning
confidence: 99%
“…The identification of potentially actionable mutation in genes other than BRCA1 and BRCA2 has led to the suggestion that panel testing should replace BRCA testing alone for most women at increased risk for breast cancer, ovarian cancer, or both . Studies have shown the ability of expanded panel testing to not only improve identification of hereditary breast and ovarian cancer predisposition but also to impact the care of both patients with and without cancer . Furthermore, panel testing is more cost effective compared to BRCA‐only testing .…”
mentioning
confidence: 99%
“…9 Studies have shown the ability of expanded panel testing to not only improve identification of hereditary breast and ovarian cancer predisposition but also to impact the care of both patients with and without cancer. 10,11 Furthermore, panel testing is more cost effective compared to BRCA-only testing. 12,13 Panel testing has now become the norm in cancer genetics programs, [14][15][16] although there are no specific guidelines regarding the optimal number of genes that should comprise a panel.…”
mentioning
confidence: 99%